A classification of factors influencing participating in collusive tendering agreements - Zarkada, Anna K. (My University, 2000)
The morality of tendering practices is an issue of economic and social significance, especially when large government contracts are involved. Criticisms are mostly concentrated around collusive tendering: illegal agreements between tenderers that result in seemingly competitive bids, price fixing or market distribution schemes that circumvent the spirit of free competition and defraud clients. Although collusion has been identified as an endemic malaise of tendering, its behavioural and moral dimensions have not been systematically studied before. The paper addresses this knowledge gap and describes part of an exploratory empirical investigation of the decision-making patterns utilised by estimators in Australia's largest construction organisations.
Keywords: Australia; Collusive tendering; Construction industry; Decision making; Marketing ethics